The relationship between pitching parameters and release points of different pitch types in major league baseball players - Hashimoto, Yasuhiro; Nagami, Tomoyuki; Yoshitake, Shinji; Nakata, Hiroki (Frontiers in Sports and Active Living, 2023)
Objectives: The purpose of this study was to deepen our understanding of pitches and to obtain basic knowledge about pitches by comparing 4-seam and other pitches in Major League Baseball (MLB). Methods: We analyzed big data for 1,820 professional baseball pitchers of MLB on release speed, spin rate, release point 3D coordinates (X, Y, and Z axes), amount of change for 4-seam, and seven changing ball types (sinker, slider, changeup, cutter, curve, split finger, and knuckle curve), using PITCHf/x and TrackMan. We also evaluated three relationships: 1) between the release points and the ball types of pitch; 2) between the amount of change in the ball and the release speed; and 3) between the release speed and the spin rate. Results: The release speed was significantly slower in seven changing ball types than in the 4-seam (p < 0.01, respectively). The spin rate and the amount of change (ΔX and ΔZ) were significantly different between 4-seam and seven changing ball types (p < 0.01, respectively). Release point 3D coordinates (X, Y, and Z axes) were significantly different between 4-seam and slider, cutter, and curve (p < 0.01, respectively). Based on these findings, the eight pitch types were mainly divided into three groups: 4-seam, curve, and off-speed pitch types. Conclusion: Seven changing ball types included specific characteristics for each parameter. The correspondence among the release speed, ΔX, and ΔZ at the 3D coordinates is an arch with 4-seam as the apex. Our results suggest an effective strategy for changing the release point and displacement of a ball’s trajectory to improve the performance of baseball pitchers.